Formation of the Religious Character of Students Through Internalization of the Values of the Hadrah and Dhuha Prayer Programs at Madrasah Ibtidaiyah - Uswah, Atiq Yufitriyah; Hartono, Hartono; Baihaqi, Wahid Ahtar (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
This study aims at immoral behavior that begins to infect elementary school children because the educational process only strengthens cognitive aspects or khalqiyah tarbiyah in al-Maraghy's terms at MI Bustanul Ulum 07 Balung, this study uses a qualitative approach with a type of field research (field research) with descriptive methods. As for data collection techniques using interviews, participant observation and documentation. The subject of this research is all student from MI Bustanul Ulum 07 Balung Jember, research draws conclusions 1) The process of character formation through dhuha prayers and hadrah activities at MI Bustanul Ulum 07 Balung can be explained in three ways. a) dhuha and hadrah prayers are an effort to form a religious culture in the school environment; b) reading asmaul husna is a means of identifying religious character; c) the process of internalizing religious values forms the character of faith, piety and love for Rasulullah 2) Factors that support the internalization of religious character are the school's cultural approach by optimizing the three centers of education.